The Mobilization of Using Cultures and Local Government’s Political-Economy Goals in Post-Reformation Banyuwangi - Ikwan Setiawan; Albert Tallapessy; Andang Subaharianto (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2017)
This article deals with an ethnic identity-based-power through the mobilization of Using cultures in Banyuwangi under local government policies in post-Reformation. By juxtaposing Foucauldian discourse, Gramscian hegemony, and political economy perspective, we discuss some cultural projects conducted by two Banyuwangi regents in post-Reformation periods, Samsul Hadi (2000-2005) and Abdullah Azwar Anas (2010-2015 and re-elected for 2016-2021 period). With different emphasized aspects, both of them created programs, which incorporated and mobilized Using cultures for accomplishing their political economy goals. Samsul legalized Using cultural expression, such as a local dance and language, as the way to strengthen the dominant-ethnic identity and reach consensus for his political authority. In more sparkling activities, Anas has transformed Using identity into various carnival programs, which, in one side, have supported tourism industry and, in other side, have helped him in gaining consensus for his hegemonic position. However, in the context of real cultural empowerment, those programs have not given positive effect for the cultural worker in the grass root.